Everybody has an Angle: The Influence of Camera Perspective on the Interpretation of Police Use of Force Videos - Korva, Natasha Michelle (Université d'Ottawa / University of Ottawa, 2022)
The increased number of video recordings circulating in the media that depict police officers exercising excessive use of force has led to recommendations to equip police officers with body worn cameras. Because a camera’s point of view may influence viewers’ perceptions and understanding of the recorded events, the angle at which a police use of force encounter is recorded may have important consequences. My program of research aimed to understand how various camera angles can impact interpretations of a police use of force scenario. A simulated police use of force incident was video recorded at three different camera angles (body worn camera, security camera, bystander camera). Study 1 (n = 330) examined factors that contribute to interpretations of the scenario such as camera angle, pre-existing attitudes about police, and information processing style. Results showed that camera angle did not have a general impact on viewer’s judgment of the scenario. However, pre-existing biases about the police and legal system guided interpretations of the scenario, and individuals who viewed the bystander video angle of the scenario rated the police officer more favourably when they endorsed positive attitudes about the police. In addition, a high need for cognition increased the likelihood of making judgments in line with participants’ attitudes about police. Study 2 (n = 576) examined the legal implications of video evidence in a depiction of a trial in which a police officer has been accused of assaulting and causing bodily harm to a complainant. Participants exposed to trial information without video evidence found the police officer less credible and more responsible for the complainant’s injury, and were more likely to recommend a guilty verdict and harsher punishment for the police officer. Individuals who were presented with trial information that included the body worn camera video evidence viewed the police officer as less credible. Attitudes and beliefs about the police and the legal system influenced decisions made regarding the police officer’s credibility, responsibility, and legal recommendations. Overall, camera perspective had an impact on interpretations of police use of force videos, but only when considering pre-existing attitudes about police, and video evidence in a criminal trial regarding police use of force impacted judgements. I discuss various practical implications of relying on police use of force videos, and present directions for future research.
Keywords: police use of force; body worn camera; camera perspective; attitudes towards police; police legitimacy; perceptions of police; information processing